Women's Football: An Examination of Factors That Influence Movement Patterns. Issue 8 (August 2020) - Griffin, Jesse; Larsen, Brianna; Horan, Sean; Keogh, Justin; Dodd, Karl; Andreatta, Melissa; Minahan, Clare
Abstract : Abstract: Griffin, J, Larsen, B, Horan, S, Keogh, J, Dodd, K, Andretta, M, and Minahan, C. Title: Women's football: An examination of factors that influence movement patterns. J Strength Cond Res 34(8): 2384–2393, 2020—The popularity and professionalism of women's football has increased in conjunction with participation rates over the last 10 years, with projected female participation rates to double worldwide by 2026. Scientific interest has also increased, in part due to Fédération Internationale de Football Association now allowing global positioning system (GPS) units to be worn during all competitive matches, resulting in investigations into the match demands of women's football. Therefore, the purpose of the present review is to provide a summary of the literature specific to the movement patterns of women's football matches. Contemporary scientific investigation using GPS match data has led to a greater understanding of the movement patterns of football. Greater emphasis has been placed on high-speed running and sprinting during matches because of the strong link to scoring opportunities and being a distinguishing factor between international and national along with elite and subelite competition levels. Further research, however, is warranted in regard to accelerations and decelerations, given the high metabolic and mechanical loads and contribution to high-speed running and sprinting. With an influx of research into the movement patterns of match-play, investigators have begun to examine factors affecting match performance such as positional demands, age, level of competition, opponent, scoreline, and phase of the game. An understanding of the factors that influence match demands is vital to ultimately be able to understand the effects on performance and how manipulating these factors may improve football performance and reduce the risk of injury.